Exploring the Urban Mediterranean Soundscapes in Cyprus and Malta: A Comparative Study - Christidis, Yiannis; Quinton, Michael (My University, 2016)
The contemporary Mediterranean Soundscape is a living organism, articulated by the ever-changing landscape, the growing building sprawl and vibrant urban activity. Accordingly, in Mediterranean Urban areas, towns’ identities are shaped partly by the rhythms of the everyday life of their inhabitants. This article approaches the contemporary soundscape of two Mediterranean places: the city centre of Nicosia in Cyprus and the urban areas of Malta. After practicing two respective soundwalks to describe the places’ sonic environments, the research uses eighteen in-depth interviews to examine the relationship between the cities’ inhabitants and their soundscape, and to explore the way people identify characteristic sounds of their place. The people of these islands appear to identify the soundscape of their place in a parallel, if not similar, way, giving particular attributes to key features of the Mediterranean soundscape. Through this study, the article outlines such similarities, as well as differences between the two soundscapes.
Keywords: Mediterranean; soundscape